Follicular dynamics and in vivo embryo production in Santa Ines ewes treated with smaller doses of pFSH - Maciel, Giovanna Serpa [UNESP] (2019)
To evaluate follicular dynamics, there was assessment of superovulatory response and in vivo embryo production in ewes treated with relatively smaller doses of exogenous pFSH than typically used in combination with a dose of eCG at the beginning of the gonadotropin treatment period. Santa Ines ewes (n = 24) were randomly divided into three groups, based on mg dose of pFSH administered: G200 (n = 8), G133 (n = 8) and G100 (n = 8) in eight decreasing doses at 12-h intervals. All ewes were treated with 300 IU of eCG concomitantly starting with first pFSH administration. Ovulatory follicular dynamics and follicular wall vascularization (FWV) were evaluated using a B-mode and color Doppler ultrasonic machine, respectively. Superovulatory response and embryo production were evaluated 6 days after estrous detection. In the G200 group, the preovulatory follicle size (PFS) were less (P < 0.05), ovulation time later (P < 0.05), and PFS rate greater (P < 0.05); while in the G100 group ovulation rate, and number and percentage of unfertilized eggs were greater (P < 0.05) than in the G133 group (P < 0.05). Number and percentage of viable embryos were greater in the G200 and G100 compared to G133 group (P < 0.05). The dose of 100 mg of FSH was as efficacious as the traditional dose of 200 mg, in combination with a dose of eCG, for superovulatory response and viable embryo production but there was a greater percentage of unfertilized eggs with this treatment.